Effects of pyrolysis atmosphere on the porous structure and reactivity of chars from middle and high rank coals (2018)
The influence of a CO2 or N2-based atmosphere on the porous structure and microstructure of the chars obtained from the slow devolatilization (10°C/min) of two coals of different rank (Semi-Anthracite (SA) and High Volatile Bituminous type C (HVBC)) and different particle size distribution was studied. Physicochemical characterization (ultimate and proximate analysis), structural and morphological characterization by Raman spectroscopy, FE-SEM, BET surface area, and volume and diameter microporous by CO2 adsorption measurements were carried out for all the chars. It was found that the kinetic parameters, the physicochemical properties, and reactivity of the chars are different, depending on the pyrolysis atmosphere. It was also determined that for char from SA coal with particle size greater than 0.7mm, the BET surface area increases when the atmosphere is enriched in CO2. This effect appears to be promoted by the interaction of different processes such as intraparticle side reactions (softening, nucleation and coalescence of bubbles, crosslinking, among others), differences in the thermal diffusivity of N2 and CO2, and the reactive effects of the latter. Additionally, tests of oxidative reactivity of chars showed that the char formed in a CO2 atmosphere is more reactive than that formed in N2. With the results of Raman analysis and kinetic parameters quantified, it was concluded that the reaction atmosphere determined the degree of ordering achieved by the char structure and that the thermo-diffusive properties of the reaction atmosphere promoted structural differences in the char even at low heating rates.